1999
DOI: 10.1002/hep.510300144
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor β and tumor necrosis factor α inhibit both apoptosis and proliferation of activated rat hepatic stellate cells

Abstract: Transforming growth factor ␤ (TGF-␤) as well as tumor necrosis factor ␣ (TNF-␣) gene expression are up-regulated in chronically inflamed liver. These cytokines were investigated for their influence on apoptosis and proliferation of activated hepatic stellate cells (HSCs). Spontaneous apoptosis in activated HSC was significantly down-regulated by 53% ؎ 8% (P F .01) under the influence of TGF-␤ and by 28% ؎ 2% (P F .05) under the influence of TNF-␣. TGF-␤ and TNF-␣ significantly reduced expression of CD95L in ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
116
0
8

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(130 citation statements)
references
References 58 publications
5
116
0
8
Order By: Relevance
“…Until now, TGF-β1 was considered as one of the most important survival factors of activated HSCs through the suppression of CD95L expression on HSCs. 41 Our findings in this study suggest that inhibition of NK cell killing of HSCs may also contribute to the important role of TGF-β1 in HSC survival.…”
Section: Discussionmentioning
confidence: 58%
“…Until now, TGF-β1 was considered as one of the most important survival factors of activated HSCs through the suppression of CD95L expression on HSCs. 41 Our findings in this study suggest that inhibition of NK cell killing of HSCs may also contribute to the important role of TGF-β1 in HSC survival.…”
Section: Discussionmentioning
confidence: 58%
“…In addition, direct interactions with ECM components leading to activation of the FAK/PI-3K-dependent survival pathway [26], and the secretion of TIMP-1 thereby preventing MMP-dependent matrix degradation [27] may promote the survival of activated HSC. Finally, autocrine stimulation by cytokines like TGF-β or IGF-1 was regarded as a potential protective mechanism [28,29]. In the in vitro model presented here, co-incubation of HSC with CM of steatotic hepatocytes significantly reduced STS-induced apoptotic cell death.…”
Section: Discussionmentioning
confidence: 84%
“…TNF-␣ is a well-known proinflammatory cytokine and can also induce apoptosis 30,31 or induce activation of hepatic stellate cells that drive fibrosis, as seen in rat models. 32,33 Other studies have shown an association between the infiltration of HBV-tetramer -CD8 ϩ T cells and an elevated ALT in chronic HBV infection but did not specifically look at the relationship of these non-HBV specific CD8 ϩ T cells to histological changes. 2,34 The frequency of intrahepatic HBV-specific TNF-␣ ϩ CD4 ϩ T cells is likely to be much lower than non-HBVspecific CD8 ϩ T cells in chronic HBV infection, but the relative importance of these populations in the generation of liver disease will be important to dissect in future studies.…”
Section: Discussionmentioning
confidence: 99%